Penyuluhan Digital Marketing Pada Masyarakat Desa Gunung Sari Kabupaten Bogor - Valentine, Hany Maria; Sudarsono, Bernadus Gunawan; Ramos, Samuel; Sharyanto, Sharyanto (LPPM Universitas Bung Karno, 2023)
The rapid development of social media has completely changed consumer behavior and also the Internet. Marketing strategies that can reach consumers through Internet usage channels, mobile devices, search engines and social media within the broadband Internet corridor are very much needed by business people. This marketing strategy is called Digital Marketing. Apart from Digital Marketing strategies that business people need to create in the 21st century. Business activities which currently coincide with the rapid development of technology must be able to compete in order to survive by utilizing marketing strategies to follow technological developments to be able to reach the target market so as to increase sales. Micro, Small and Medium Enterprises (MSME) business people have used Digital Marketing technology independently during Covid-19, via WhatsApp, Facebook or Instagram. In this regard, the people of the village of Gunung Sari, Pamijahan District, Bogor Regency needs additional Digital Marketing knowledge so that the business activities carried out can continue and get additional funds to help the family economy. In particular, Digital Marketing is digital literacy which is needed to increase the knowledge and abilities of village communities in reducing the negative impacts of digitalization and creating business opportunities utilizing digital platforms. Because the village of Gunung Sari, Pamijahan District, Bogor Regency needs to be equipped with Digital Marketing skills as a form of digital literacy. The Faculty of Computer Science, Department of Information Systems, Bung Karno University carries out a community service program by sharing knowledge and providing community outreach, especially the community in Gunung Sari Village, Pamijahan District, Bogor Regency.